Penerapan Pasal 68 Ayat 1 Jo Pasal 4 Dan 6 Undang-Undang No.15 Tahun 2001 Dalam Penyelesaian Sengketa Merek Kok Tong Kopitiam pada Putusan No. 05/Merek/2010/PN.Niaga Medan - Desriyana, Desriyana; Hasibuan, H.A. Lawali (Jurnal Ilmiah Penegakan Hukum, 2017)
Application of Article 68 Paragraph 1 Jo Article 4 and 6 of Law No. 15 of 2001 in Brand Dispute Resolution Kok Tong Kopitiam of Decision No. 05 / Merek / 2010 / PN.Niaga MedanAbstractBrands are the result of human thought and intelligence which can take the form of discovery. Brands are used as a differentiator between products produced by a person or legal entity with products produced by other parties. The current journey to free trade, aspects of intellectual property rights, will play a very important role in national and international trade. Intellectual property rights are rights that arise or are born due to human intellectual abilities in the form of findings, works, creations or creations in the field of technology, science, art and literature. Based on Article 68 paragraph (1) of Law Number 15 of 2001 which states that "Brand cancellation claims can be filed by interested parties based on the reasons referred to in Article 4, Article 5, and Article 6. This type of research is normative juridical namely research which is focused on reviewing the application or rules or norms in positive law. The nature of this research is analytical descriptive, which carefully describes the characteristics of the facts to determine the frequency of something that happens. The purpose of this study was to find out the judge's consideration in resolving the dispute over the Kong Tong Kopi Tiam brand and to find out the relationship between Article 68 paragraph (1) Jo. Articles 4 and 6 of Law Number 15 of 2001 in the resolution of the Kok Tong Kopi Tiam brand dispute.